Evaluasi Kualitas Layanan terhadap Operator Telekomunikasi: Tinjauan Perspektif Pelanggan - Armin Darmawan; Mulyadi Mulyadi; Fauziah Fauziah (Jurnal Optimasi Sistem Industri, 2017)
This study examines the quality level of service in one of the telecommunication operator (mobile network provider) in Makassar. This paper focuses on the identification of the gaps, mapping quality level of service, and the evaluation of the service quality level. The study was conducted using SERVQUAL approach which refers to the five dimensions of service quality. SERVQUAL is helpful in identifying, mapping, and analyzing the gap level between expectations and perceptions of a telecommunication service. Questionnaires were randomly distributed to the 400 respondents’ mobile telecommunication users in Makassar. The results show that there were 10 negative attributes on the SERVQUAL value of 15 questions. This indicates that the service quality to the users is at the low level. For mapping and prioritization of services related attributes that need to be improved, this study used the Importance-Performance Analysis (IPA) diagram. The first quadrant indicates a high level of customer expectations relative to those attributes but on the perception remains low. The first quadrant is a mapping attribute which is prioritized in the improvement of service quality related to the reliability dimensions i.e the improvement of network quality, network expansion, and the affordable cost of access (Internet, telephone, and SMS).